Analysis of The Implementation of The Autogate Policy at The Immigration Inspection Are of I Gusti Ngurah Rai International Airport, Bali - Yuditya Eka Mandala Putra; I Wayan Sutrisna; I Gde Surya Kurniawan (International Journal Labs, 2025)
The rapid growth of the tourism sector in Bali has increased the volume of passengers at I Gusti Ngurah Rai International Airport and put pressure on immigration services. As a solution, the Indonesian government has implemented a policy of using Autogate to speed up the inspection process and improve the quality of service. This study aims to analyze the implementation of the Autogate policy at Ngurah Rai Airport, identify factors that influence its success, and provide recommendations for improvement. This study uses a qualitative approach with a descriptive method. Data were collected through in-depth interviews with immigration officers, service users, and direct observations in the field. The results of the study indicate that the implementation of Autogate has succeeded in increasing efficiency and user satisfaction. However, there are still several challenges such as lack of socialization, technical errors, and user behavior that need to be addressed. This study concludes that the implementation of Autogate is the right step to improve the quality of immigration services at Ngurah Rai Airport. However, there needs to be ongoing efforts to improve socialization, improve the system, and change user behavior so that the benefits of this technology can be optimal.